Magnesio-riebeckite from the Varenche mine (Aosta Valley, Italy): crystal-chemical characterization of a grandfathered end-member. (1st December 2017) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank; Ciriotti, Marco
Magnesio-riebeckite from the dumps of the abandoned mine of Varenche (45°47'22'' N, 7°29'17'' E), Saint-Barthélemy, Nus, Aosta Valley (Italy), was studied to provide the complete mineral description (including crystal structure) and insights into the crystal-chemistry of riebeckite. The empirical formula derived from electron microprobe analysis and single-crystal structure refinement is A(Na0.09K0.01)∑=0.10B(Na1.77Ca0.11Mg0.08Mn2+0.04)∑=2.00C(Mg2.93Mn2+0.13Fe2+0.07Zn0.01Ni0.12Fe3+1.25Al0.48Ti0.01)∑=5.00T(Si7.92Al0.08)∑=8.00 O22W(OH1.88F0.12)∑=2.00. Magnesio-riebeckite is biaxial (+), with α = 1.678(2), β = 1.682(2), γ = 1.688(2) and 2V (meas.) = 80.2(1.7)°, 2V (calc.) = 78.7°. The unit-cell parameters are a = 9.6481(14), b = 17.873(3), c = 5.3013(7) Å, β = 103.630(2)°, V = 888.4 (2) Å3, Z = 2, space group C2/m. The strongest ten reflections in the powder X-ray pattern [d values (in Å), I, (hkl)] are: 2.701, 100, (151); 8.303, 83, (110); 3.079, 62, (310); 3.391, 53, (131); 4.467, 50, (040, 021); 2.522, 50, (202); 2.578, 35, (061); 2.155, 30, (261), 4.855, 30, (111), 2.300, 29, (351).